2D nanosheet molybdenum disulphide (MoS2) modified electrodes explored towards the hydrogen evolution reaction. Issue 43 (19th October 2015) - Rowley-Neale, Samuel J.; Brownson, Dale A. C.; Smith, Graham C.; Sawtell, David A. G.; Kelly, Peter J.; Banks, Craig E.
Abstract : 2D molybdenum disulphide nanosheets are explored as an electrocatalyst towards the hydrogen evolution reaction (HER) using modified carbon based electrodes. Abstract : We explore the use of two-dimensional (2D) MoS2 nanosheets as an electrocatalyst for the Hydrogen Evolution Reaction (HER). Using four commonly employed commercially available carbon based electrode support materials, namely edge plane pyrolytic graphite (EPPG), glassy carbon (GC), boron-doped diamond (BDD) and screen-printed graphite electrodes (SPE), we critically evaluate the reported electrocatalytic performance of unmodified and MoS2 modified electrodes towards the HER. Surprisingly, current literature focuses almost exclusively on the use of GC as an underlying support electrode upon which HER materials are immobilised. 2D MoS2 nanosheet modified electrodes are found to exhibit a coverage dependant electrocatalytic effect towards the HER. Modification of the supporting electrode surface with an optimal mass of 2D MoS2 nanosheets results in a lowering of the HER onset potential by ca. 0.33, 0.57, 0.29 and 0.31 V at EPPG, GC, SPE and BDD electrodes compared to their unmodified counterparts respectively. The lowering of the HER onset potential is associated with each supporting electrode's individual electron transfer kinetics/properties and is thus distinct. The effect of MoS2 coverage is also explored. We reveal that its ability to catalyse the HER is dependent on the mass deposited until a critical mass of 2D MoS2 nanosheets is achieved, after which its electrocatalytic benefits and/or surface stability curtail. The active surface site density and turn over frequency for the 2D MoS2 nanosheets is determined, characterised and found to be dependent on both the coverage of 2D MoS2 nanosheets and the underlying/supporting substrate. This work is essential for those designing, fabricating and consequently electrochemically testing 2D nanosheet materials for the HER.